2021
DOI: 10.12688/wellcomeopenres.16106.3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intimate partner violence and abuse among adolescents and young adults: findings from a UK population-based cohort

Abstract: Background: Approximately one-third of young people in the UK have suffered intimate partner violence and abuse (IPVA) on reaching adulthood. We need interventions to prevent IPVA in this population, but there is a lack of evidence on who is at greatest risk. Methods: We analysed questionnaire data from 3,279 participants of the Avon Longitudinal Study of Parents and Children population-based birth cohort. We estimated the prevalence of IPVA victimisation and perpetration by age 21, by sex, demographic, parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Seven studies (21.8%) measured dating violence as a global variable as opposed to examining different types of violence. These studies found that the perpetration of dating violence is related to various adverse childhood experiences: physical abuse [ 24 , 73 ], emotional abuse [ 24 , 73 ], sexual abuse [ 24 ], physical and emotional neglect [ 58 , 73 ], low parental warmth [ 58 ], parental mental illness, parental suicide attempt, parental criminal conviction, and parental separation [ 24 ]. However, some of these studies did not report a positive association between perpetration and sexual abuse [ 58 , 67 ], interparental violence, parental substance abuse [ 24 ], or violent socialisation in childhood [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies (21.8%) measured dating violence as a global variable as opposed to examining different types of violence. These studies found that the perpetration of dating violence is related to various adverse childhood experiences: physical abuse [ 24 , 73 ], emotional abuse [ 24 , 73 ], sexual abuse [ 24 ], physical and emotional neglect [ 58 , 73 ], low parental warmth [ 58 ], parental mental illness, parental suicide attempt, parental criminal conviction, and parental separation [ 24 ]. However, some of these studies did not report a positive association between perpetration and sexual abuse [ 58 , 67 ], interparental violence, parental substance abuse [ 24 ], or violent socialisation in childhood [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…These same studies reported a positive relationship between dating violence victimisation and adverse childhood experiences such as: physical abuse [ 24 , 51 , 58 , 64 , 73 ], emotional abuse [ 24 , 73 ], sexual abuse [ 24 , 39 , 51 , 64 ], physical and emotional neglect [ 49 , 67 ], witnessing interparental violence [ 24 , 51 ], low parental warmth [ 58 ], substance abuse, mental illness, suicide attempts, criminal conviction, and parental separation [ 24 ]. However, other studies did not support an association between dating violence victimisation and violent socialisation in childhood [ 67 ], sexual abuse [ 67 , 73 ], emotional neglect or interparental violence [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PSCP implementation request by the IPV victim must be made freely and clearly but all involved parties must agree. It is important to acknowledge whether risk factors identified in the literature were considered in this decision (Campbell et al, 2008;Messing et al, 2017;Herbert et al, 2021). Risk factors may include the type of violence inflicted, firearm access, personal perception of risk by victims, jealousy and possessiveness, stalking and threats, mental disorder, substance abuse, and previous criminal record (Rodrigues et al, 2021;Vieira-Pinto et al, 2021).…”
Section: Pscp Determinantsmentioning
confidence: 99%